2000
DOI: 10.1074/jbc.m002750200
|View full text |Cite
|
Sign up to set email alerts
|

The Inositol Hexakisphosphate Kinase Family

Abstract: Saiardi et al. (Saiardi, A., Erdjument-Bromage, H., Snowman, A., Tempst, P., and Snyder, S. H. (1999) Curr. Biol. 9, 1323-1326) previously described the cloning of a kinase from yeast and two kinases from mammals (types 1 and 2), which phosphorylate inositol hexakisphosphate (InsP 6 ) to diphosphoinositol pentakisphosphate, a "high energy" candidate regulator of cellular trafficking. We have now studied the significance of InsP 6 kinase activity in Saccharomyces cerevisiae by disrupting the kinase gene. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 168 publications
(134 citation statements)
references
References 37 publications
(81 reference statements)
5
127
2
Order By: Relevance
“…We now report the cloning and characterization of mammalian IPMK (mIPMK). We have discovered an unprecedented substrate specificity whereby mIPMK can synthesize InsP 3 (14). All of the radiolabeled inositol phosphates that we synthesized were purified by HPLC and desalted (15).…”
mentioning
confidence: 99%
“…We now report the cloning and characterization of mammalian IPMK (mIPMK). We have discovered an unprecedented substrate specificity whereby mIPMK can synthesize InsP 3 (14). All of the radiolabeled inositol phosphates that we synthesized were purified by HPLC and desalted (15).…”
mentioning
confidence: 99%
“…In mammals, such events might involve differential expression of the three isoforms of IP 6 kinase, because each has different affinities for the competing IP 5 and IP 6 substrates (12, 13). Unfortunately, perhaps, the one isoform of IP 6 kinase that is predominantly nuclear (type 2) has the weakest ability to phosphorylate IP 5 to PP-IP 4 (12,13). Furthermore, no one has yet shown that there is an extracellular stimulus that can specifically regulate PP-IP 4 levels, thereby providing opportunities for telomere length to be regulated independent of the many effects that other inositol pyrophosphates can elicit (see above).…”
Section: A New Role For Pp-ip 4 ?mentioning
confidence: 99%
“…Only one homologue, Kcs1, has been cloned from Saccharomyces cerevisiae (18). All IP6 kinases also phosphorylate IP5 to PP-IP4 (12). Not shown is the hydrolysis of the diester phosphates by specific phosphohydrolases (19).…”
Section: Regulation Of Telomere Lengthmentioning
confidence: 99%
“…IP6 is not the only substrate for IP6K1 and IP6K2. Both IP6Ks can also phosphorylate IP5 to yield PP-IP4 (32). Because PEI-TLC could not clearly resolve PP-IP5 and PP-IP4, it is possible the latter compound may also contribute to growth inhibition and apoptosis.…”
Section: Table I Effect Of Ifns On Induction Of Apoptosis In Nih-ovcamentioning
confidence: 99%
“…Inositol PP include PP-IP5 (7 phosphates/inositol), bis-PP-IP4 (8 phosphates/inositol) (31), PP-IP4 (6 phosphates/inositol), and bis-PP-IP3 (7 phosphates/inositol) (32). The specific functional roles of PP-IP5, bis-PP-IP4, and their precursor, IP6, are not clearly understood.…”
Section: Table I Effect Of Ifns On Induction Of Apoptosis In Nih-ovcamentioning
confidence: 99%